2019
DOI: 10.1002/tcr.201900023
|View full text |Cite
|
Sign up to set email alerts
|

NH3‐Driven Benzene C−H Activation with O2 that Opens a New Way for Selective Phenol Synthesis

Abstract: Catalytic benzene C−H activation toward selective phenol synthesis with O2 remains a stimulating challenge to be tackled. Phenol is currently produced industrially by the three‐steps cumene process in liquid phase, which is energy‐intensive and not environmentally friendly. Hence, there is a strong demand for an alternative gas‐phase single‐path reaction process. This account documents the pivotal confined single metal ion site platform with a sufficiently large coordination sphere in β zeolite pores, which pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Zeolite Y-supported alkali metal ion and alkaline earth metal ion catalysts were prepared by a reliable ion-exchange method, , followed by a controlled treatment at 573 K, using the corresponding metal nitrates as precursors. A typical Cs + (2 wt %)/Y sample was synthesized as follows.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeolite Y-supported alkali metal ion and alkaline earth metal ion catalysts were prepared by a reliable ion-exchange method, , followed by a controlled treatment at 573 K, using the corresponding metal nitrates as precursors. A typical Cs + (2 wt %)/Y sample was synthesized as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we found a single alkali metal ion site platform in a β zeolite pore that selectively promoted benzene C sp2 −H activation toward phenol synthesis. 1,2 The catalytic performance of alkali metal ion sites incorporated in zeolite pores depended strongly on the kind of zeolites, and ZSM-5, mordenite, and Y zeolites were almost inactive as supports. No C sp3 −H activation catalysis of alkali metal ions and oxides has been achieved to date, although a variety of effects of alkali metal additives on metal oxide catalysis are known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkali and alkaline-earth metal-ion (M n + ) single site catalysts in β-zeolite pores (M n + : Na + , Mg 2+ , K + , Ca 2+ , Rb + , Sr 2+ , Cs + , Ba 2+ ) were prepared by a reliable ion-exchange method using the corresponding metal nitrates as precursors in a similar way to that in our previous study. In the present study, the obtained samples were activated and stabilized by calcination at 500 °C for 1 h. Typically, a Cs + (1 wt %)/β sample was synthesized as follows. CsNO 3 (0.146 g) was dissolved in 10 mL of deionized water in a 50 mL Erlenmeyer flask, to which solution 9.9 g of NH 4 + -β with SiO 2 /Al 2 O 3 = 25 (molar ratio) was added with stirring.…”
Section: Methodsmentioning
confidence: 96%
“…However, recently, we reported that a Cs + single site/β catalyst without a beneficial redox property showed catalytic benzene C sp 2 −H hydroxylation with N 2 O or O 2 + NH 3 toward phenol in gas phase. 42,43 We also reported that a Cs + single site/Y catalyst, which was inactive for the benzene hydroxylation, showed a high efficiency for the selective ammoxidation of toluene and its derivatives with O 2 + NH 3 in gas phase. 44 In the present study, we have found unprecedented efficient performances of Cs + single-ion sites confined in β-zeolite channels (1 wt % Cs + -loading) for selfand cross-aldol condensation reactions involving C−C bond formation in liquid phase for the first time.…”
Section: ■ Introductionmentioning
confidence: 98%